THE IMPACT OF INFLATION ON ECONOMIC GROWTH: A COMPREHENSIVE LITERATURE STUDY - Loso Judijanto; Iwan Kusnadi, Wahab (JOURNAL OF COMMUNITY DEDICATION, 2024)
The general rise in prices of goods and services that occurs in a country is called inflation, an economic phenomenon. Its impact on economic growth can vary depending on its level and stability. Controlled inflation is often considered a sign of economic health as increased demand for goods and services drives economic activity, investment and increased wealth. Conversely, runaway inflation or hyperinflation can undermine confidence in the domestic currency, reduce consumer purchasing power and weaken economic growth. In addition, inflation also has a major effect on investment and savings. High inflation lowers the real value of savings, makes saving less attractive, and encourages short-term consumption. This can reduce resources for long-term investment needed for sustainable growth. Uncertainty due to uncontrolled inflation can discourage companies from making new investments or expanding business, leading to economic stagnation. Therefore, maintaining a stable and predictable inflation rate is a key challenge for economic policies supporting long-term growth.